Finnish university students' knowledge of the health impacts of postponing childbearing, Finland 2011. Issue 3 (4th May 2017) - Nipuli, Suvi; Hemminki, Elina; Rämö, Antti; Klemetti, Reija
Abstract : Introduction: Aging motherhood is an individual but also a public health issue. In Western countries, postponing parenthood is common especially among the highly educated. Objective: The objective was to assess Finnish university students' knowledge of the effect of age on fertility and age-related health risks for pregnancy and children. The second objective was to examine students' own estimation of their knowledge about age-related fertility and pregnancy risks. Methods: Data were collected by anonymous questionnaires among university students with a consecutive sampling method in Finnish universities in 2011. Of the 2057 invited students, 67% ( n = 1368) participated. Raw and age-stratified cross-tabulations by sex were calculated. Logistic regressions to analyze the relation between knowledge and students' background characteristics were made, adjusting for other characteristics. Results: 14% of female and 29% of male students did not know that it is more difficult for women aged 35 years to become pregnant compared to women aged 25 years. The critical period for decreasing female fertility with age (30–35 years) was unknown by 36% of female and 54% of male students. Of female students, 10% did not know that the pregnancy risks for women aged over 35 years are increased and 20% did not know that age increases the risks for the child. About half of the students felt that they had not received enough information about age-related fertility and pregnancy risks. Sex, age, a stable relationship, studying health sciences, and students' own estimation of their knowledge were significantly associated with knowing the correct answers. Conclusions: Awareness of age-related fertility was insufficient and students thought that they did not have enough information. Due to the increased proportion of women and men delaying childbearing, young adults need information so as to make informed reproductive choices.